Ambiguous-cue interpretation is biased under stress- and depression-like states in rats - Enkel, Thomas; Gholizadeh, Donya; von Bohlen und Halbach, Oliver; Sanchis-Segura, Carles; Hurlemann, Rene; Spanagel, Rainer; Gass, Peter; Vollmayr, Barbara (Neuropsychopharmacology, 2010)
Negative cognitive bias - the tendency to interpret ambiguous situations pessimistically - is a central feature of stress-related disorders such as depression. The underlying neurobiology of this bias, however, remains unclear, not least because of a lack of translational tools. We established a new ambiguous-cue interpretation paradigm and, with respect to the etiology of depression, evaluated if environmental and genetic factors contribute to a negative bias. Rats were trained to press a lever to receive a food reward contingent to one tone and to press another lever in response to a different tone to avoid punishment by electric foot-shock. In the ambiguous-cue test, the lever-press responses to tones with frequencies intermediate to the trained tones were taken as indicators for the rats' expectation of a positive or negative event. A negative response bias because of decreased positive and increased negative responding was found in congenitally helpless rats, a genetic animal model of depression. Moreover, treatment with a combined noradrenergic-glucocorticoid challenge, mimicking stress-related changes in endogenous neuromodulation, biased rats away from positive responding. This response shift was accompanied by neuronal activation in dentate gyrus and amygdala. Thus, environmental and genetic risk factors for depression induce a response bias, which resembles the pessimistic bias of patients suffering from depression. The behavioral paradigm described constitutes a useful tool to study the neuronal basis of decision making under ambiguous conditions and may promote innovative pharmaco- and psychotherapy for depression.